The effect of probiotics on the diarrhea and constipation outcomes in children: an umbrella review of systematic reviews and meta-analyses - Wang, Qizheng; Ren, Tailiang; Wang, Haijun; Lin, Xiaofei (Frontiers in Nutrition, 2025)
BackgroundThe existing literature on the effects of probiotics on diarrhea and constipation outcomes remains inconsistent. Therefore, this umbrella review of systematic reviews and meta-analyses aims to provide a concise and definite understanding in relation to the effect of probiotics on diarrhea and constipation in children.MethodsA comprehensive systematic search was carried out in on Scopus, PubMed, Embase, Web of Science, and Google Scholar up to December 2024. The overall effect size was calculated using random effect model. Also, subgroup analyses were performed regarding age group, health condition, single or multi-strain probiotics.ResultsThis umbrella study comprises a systematic review of 35 studies. Our findings illustrated that probiotics reduce odds [odds ratio (OR) = 0.51; 95% confidence interval (CI): 0.27, 0.94] and risk of diarrhea incidence [relative risk (RR) = 0.54; 95% CI: 0.40, 0.71] compared to control group, meaningfully. Also, it is successful in reducing diarrhea duration [weighted mean difference (WMD) = −1.85; 95% CI: −2.83, −0.86] and [standardized mean difference (SMD) = −0.94; 95% CI: −1.32, −0.56] significantly. Moreover, probiotics supplementation resulted in decreased stool frequency (WMD = −0.21; 95% CI: −0.37, −0.04). Probiotics prevent diarrhea by about 36% (RR = 0.64; 95% CI: 0.63, 0.65(, and significantly improved diarrhea treatment (SMD = −0.49; 95% CI: −0.59, −0.38). Also, the analyses revealed that probiotics significantly impact on constipation (OR = 1.17, 95% CI: 1.01–1.37).ConclusionThis meta-analysis supports the potential role of probiotics in relation to diarrhea and constipation outcome in children. Probiotic supplementation contributed to a declined risk and odds of diarrhea incidence. Also, probiotic supplementation was accompanied with decreased diarrhea duration.